Between republic and empire : interpretations of Augustus and his principate - Raaflaub, Kurt A.; Toher, Mark; Bowersock, G. W. (Glen Warren), 1936- (University of California Press, 1990)
"The Romans themselves held sharply divided opinions about Augustus's regime. Augustus seized power through violence and civil war and profoundly transformed state and society; but he also pacified the empire, stabilized the government, and remedied fatal weaknesses of the republic. Representing five major areas of Augustan scholarship -- historiography, poetry, art, religion, and politics -- the nineteen contributors to this volume offer penetrating analyses of questions fundamental to a new assessment, bringing us closer to a balanced, up-to-date account of Augustus and his principate. Book jacket."--Jacket